Modeling Meridians Within the Quantum Field Theory - Larissa Brizhik; Enrico Chiappini; Patrizia Stefanini; Giuseppe Vitiello (Medical Association of Pharmacopuncture Institute, 2019)
We present here a model of meridians in the formalism of the gauge theory paradigm of quantum field theory with spontaneous breakdown of symmetry. We discuss the origin and dynamic self-focusing propagation of the electromagnetic field in coherent states and the role it plays in our meridian modeling. Within this frame, we consider the formation of solitary waves on proteins and anatomical filamentary structures and discuss nondissipative energy transport. Finally, we analyze the relation of meridians with anatomical filamentary structures, the reciprocal actions between meridians, and biochemical activity and the key role played by free energy, internal energy, and entropy. Keywords: coherence, energy transfer, meridians, solitons, spontaneous breakdown of symmetry